A Descriptive Review of Global Real World Evidence Efforts to Advance Drug Discovery and Clinical Development in Amyotrophic Lateral Sclerosis - Cook, Suzanne F.; Rhodes, Thomas; Schlusser, Courtney; Han, Steve; Chen, Chao; Zach, Neta; Murthy, Venkatesha; Davé, Shreya (Frontiers in Neurology, 2021)
Understanding patient clinical progression is a key gateway to planning effective clinical trials and ultimately enabling bringing treatments to patients in need. In a rare disease like amyotrophic lateral sclerosis (ALS), studies of disease natural history critically depend on collaboration between clinical centers, regions, and countries to enable creation of platforms to allow patients, caregivers, clinicians, and researchers to come together and more fully understand the condition. Rare disease registries and collaborative platforms such as those developed in ALS collect real-world data (RWD) in standardized formats, including clinical and biological specimen data used to evaluate risk factors and natural history of disease, treatment patterns and clinical (ClinROs) and patient- reported outcomes (PROs) and validate novel endpoints. Importantly, these data support the development of new therapeutics by supporting the evaluation of feasibility and design of clinical trials and offer valuable information on disease trajectory and outcomes outside of the clinical trial setting for comparative purposes. RWD may help to accelerate medicines development by identifying and validating outcome measures and disease subpopulations. RWD can also make potential contributions to the evaluation of the safety and effectiveness of new indications for approved products and to satisfy post-approval regulatory and market access requirements. There is a lack of information on available registries, databases, and other sources of real-world data on ALS; thus, a global review of all available resources was warranted. This targeted review identifies and describes ALS registries, biobanks and collaborative research networks that are collecting and synthesizing RWD for the purposes of increasing patient awareness, advancing scientific knowledge, and informing the development of novel, safe and effective treatments and therapies.